Hierarchical porous NiCo2O4@Ni as carbon-free electrodes for Lithium–oxygen batteries. (20th June 2015) - Lin, Xiujing; Su, Junming; Li, Liangyu; Yu, Aishui
Abstract: A carbon-free, three-dimensional network structured material composed of NiCo2 O4 nanowires and Ni foam was synthesized by a facile method. When applied as the air electrode for the lithium–oxygen battery, the unique network structure enables the surface of nanowires highly accessible to the reactants and facilities the electron transport during the charge/discharge processes. A superior electrochemical performance including low charge overpotential and excellent cyclability are obtained. This work suggests the great potential of the carbon-free NiCo2 O4 @Ni as the air electrodes for lithium–oxygen batteries.